(untitled) (Research, Society and Development, 2022)
Measles is an extremely contagious infectious exanthematous disease whose etiological agent is an RNA virus of the genus Morbillivirus, belonging to the Paramyxoviridae family. The transmission occurs through nasopharyngeal secretions of infected people. Brazil has suffered a measles outbreak since 2018 and the means of prevention, control, and eradication is the triple viral and tetra viral vaccine, however, in recent years the percentage of vaccination coverage has been reducing, especially in the North, where Pará is the state with the lowest vaccination percentage. This study aimed to evaluate the process of epidemiological surveillance of vaccination coverage, considering the measles outbreak in the state of Pará. The spatial distribution of cases in the municipalities of Pará was performed in the QGIS software (version 3.10.2 A Coruña) and vaccination coverage by the National Immunization Program Information System provided by the DATASUS platform and tabulated in Microsoft Excel spreadsheets. The study showed that between the years 2010 to 2012 the vaccination coverage in the state was within the established goal, declining significantly from 2013 reaching in 2022 to 17%, leading in 2018 the reintroduction of the virus, registering in 2020, 4,841 cases of measles, the most affected sex was male and the age range was between 15 to 29 years and children under one year. We conclude that there is an urgent need for preventive measures in the state in order to recover the certification of measles in Brazil.